Kinetika Perubahan Kualitas Fisik Buah Mangga Selama Pengeringan Beku dengan Perlakuan Pendinginan Awal dan Ketebalan Irisan - Yulia Ariani; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Mango (Mangifera indica L.) is one of the important fruits for tropical residents. The biggest losses of mangoes occur during the postharvest period due to the lack of proper postharvest handling and lack of processing efforts. Frozen drying is a method that is considered the best at present for preserving horticultural products. This freeze drying method can maintain the structure, taste, color, and aroma of fruit. In this method, the product was cooled to freeze for 6 hours. The solid phase water was then removed from the material through a sublimation process in vacuum condition. This study aimed to find out the freeze drying results through various pre-treatments and thicknesses by means of determining the proper combination treatment. The mango used had a sweetness level of 18° Brix with a size of 14 cm x 8 cm and an average weight of 400 g. This research was conducted using a three-factor completely randomized design of 2 x 3 x 5. The first factor was the cooling treatment (non-freezing and liquid nitrogen). The second factor was the thickness of the material (0.5 cm, 1 cm and 1.5 cm). The third factor was time (0 hours, 9 hours, 18 hours, 27 hours and 36 hours). The observed parameters comprised of: water content, texture, and lightness. The non-freezing treatment with 1.5 cm thickness showed a low water content of 7.58%, and the kinetics results used the Newtonian model. It also showed the highest vitamin C decrease, that was 84.12% and the kinetics results used the first-order model. The highest lightness decrease of liquid nitrogen treatment with 1 cm thickness was 74.08%.